Demystifying the German 'Armament Miracle' During World War II. New Insights from the Annual Audits of German Aircraft Producers - Lutz Budraß; Jonas Scherner; Jochen Streb (Yale University, Economic Growth Center, 2005)
Armament minister Albert Speer is usually credited with causing the boom in German armament production after 1941. This paper uses the annual audit reports of the Deutsche Revisions- und Treuhand AG for seven firms which together represented about 50 % of the German aircraft producers. We question the received view by showing that in the German aircraft industry the crucial changes that triggered the upswing in aircraft production already occurred before World War II. The government decided in 1938 that aircraft producers had to concentrate on a few different types, and in 1937 that cost-plus contracts were replaced with fixed price contracts. What followed was not a sudden production miracle but a continuous development which was fuelled first by learning-by-doing and then by the ongoing growth of the capital and labor endowment.
Keywords: H57; L64; N44; 330; German armament miracle; World War II; Albert Speer; Aircraft industry; Learning-by-doing; Fixed-price Contract; Labor productivity; Rüstungspolitik; Rüstungsindustrie; Luftfahrtindustrie; Lernprozess; Arbeitsproduktivität; Deutschland (bis 1945)